Androgen Receptor Silences Thioredoxin‐interacting Protein and Competitively Inhibits Glucocorticoid Receptor‐Mediated Apoptosis in Pancreatic β‐Cells. Issue 6 (10th April 2015) - Harada, Naoki; Katsuki, Takahiro; Takahashi, Yuji; Masuda, Tatsuya; Yoshinaga, Mariko; Adachi, Tetsuya; Izawa, Takeshi; Kuwamura, Mitsuru; Nakano, Yoshihisa; Yamaji, Ryoichi; Inui, Hiroshi
ABSTRACT: Androgen receptor (AR) is known to bind to the same cis ‐element that glucocorticoid receptor (GR) binds to. However, the effects of androgen signaling on glucocorticoid signaling have not yet been elucidated. Here, we investigated the effects of testosterone on dexamethasone (DEX, a synthetic glucocorticoid)‐induced apoptosis of pancreatic β‐cells, which might be involved in the pathogenesis of type 2 diabetes mellitus in males. We used INS‐1 #6 cells, which were isolated from the INS‐1 pancreatic β‐cell line and which express high levels of AR. Testosterone and dihydrotestosterone inhibited apoptosis induced by DEX in INS‐1 #6 cells. AR knockdown and the AR antagonist hydroxyflutamide each diminished the anti‐apoptotic effects of testosterone. AR was localized in the nucleus of both INS‐1 #6 cells and pancreatic β‐cells of male rats. Induction of thioredoxin‐interacting protein (TXNIP) is known to cause pro‐apoptotic effects in β‐cells. Testosterone suppressed the DEX‐induced increase of TXNIP at the transcriptional level. A Chromatin immunoprecipitation assays showed that both AR and GR competitively bound to the TXNIP promoter in ligand‐dependent manners. Recombinant DNA‐binding domain of AR bound to the same cis ‐element of the TXNIP promoter that GR binds to. Our results show that AR and GR competitively bind to the same cis ‐element of TXNIP promoter as a silencer and enhancer, respectively. These results indicate that androgen signaling functionally competes with glucocorticoid signaling in pancreatic β‐cell apoptosis. J. Cell. Biochem. 116: 998–1006, 2015. © 2015 Wiley Periodicals, Inc.